Numerical Study of Flow Pattern in Buildings with Different Heights - Ali Hooshmand Aini (Salehan Institute of Higher Education, 2016)
Understanding the flow pattern around the building, results in an accurate analysis of structure performance. Furthermore, having a proper configuration of the buildings next to each other we can provide a situation in which the buildings use the wind to make the air movement and natural ventilation. In this paper we use the FLUENT software to verify numerical flow pattern in buildings with different heights, and the results are provided in the form of distribution of velocities, velocity in Y direction, flow patterns and counters of turbulent.